2019
DOI: 10.1088/1755-1315/278/1/012073
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of fishermen communities against the establishment of conservation areas in Pongok Island, South Bangka

Abstract: Pongok Island has the potential of coastal ecosystems, namely mangrove, seagrass, and coral reef. Recently, increasing use of bombs and potassium in fishing can be destructive hence the ecosystems need to be conserved in order to be utilized sustainably. The management in question is the establishment of a conservation area that involves fishing communities so that an assessment of the community’s perception of the determination of conservation areas is needed. This study aims to determine the perception of fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…These measures aim to minimize the burden on affected species and encourage sustainable fishing techniques. Soeprijadi et al [38] have identified the fishing population on Pongok Island is supportive of the conservation zone establishment. They understand the value of maintaining resources like mangroves, coral reefs, and seagrasses for their ecological services and resource availability.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These measures aim to minimize the burden on affected species and encourage sustainable fishing techniques. Soeprijadi et al [38] have identified the fishing population on Pongok Island is supportive of the conservation zone establishment. They understand the value of maintaining resources like mangroves, coral reefs, and seagrasses for their ecological services and resource availability.…”
Section: Resultsmentioning
confidence: 99%
“…They also provide nutrients and plankton abundance that are needed by a different trophic food web. Pongok Islands have a complete coastal ecosystem such as mangroves, seagrass beds, and coral reefs [38]. The seashore of this island is surrounded by mangrove forests consisting of three notable species: Rhizophora sp., Sonneratia sp., Avicenia sp., and Brugiera sp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation